Business Plan for English Language School (ELS) in Tajikistan - Oymukhamedova, Lyubov (2016)
English Language School (ELS) is a startup organization that intends to provide the high-quality tutoring services of English as a foreign language in Dushanbe city, Republic of Tajikistan. The ELS is positioning itself to become a market leader in offering the high standard of tutoring services through adapting international tutoring techniques. The school possesses qualification that will meet accreditation requirements of the international recognized educational organization. The idea came from the expert of the centre who informally provided tutoring services for the last 10 years having a high demand among students. Thus, it was decided to concentrate on developing this business into a new effective source of a high standard of English language knowledge. This business plan sets out our strategic, operating and financial goals for the next three years.